iohanetc

2021-08-11

To solve:
$3\left(x-1.1\right)=5x-5.3$

Szeteib

Step 1
$3\left(x-1.1\right)=5x-5.3$
Distributive property, $a\left(b-c\right)=ab-ac$
Substitute $a=3,b=x$ and $c=1.1$ in $a\left(b-c\right)=ab-ac$
$3\left(x-1.1\right)=3\left(x\right)-3\left(1.1\right)$
$3×1.1$
Based on the definition,
Multiply the decimals as though they are whole numbers.
$3×1.1$
$=33$
The decimal point in the product is placed so that the number of decimal places in the product is equal to the sum of the sum of the number decimal places in the factors.
The number decimal places in the factors is 1.
So, place decimal point from one number from right.
$3.3$
$3\left(1.1\right)=3.3$
$3\left(x\right)=3x$
Substitute $3\left(1.1\right)=3.3$ and $3\left(x\right)=3x$ in $3\left(x-1.1\right)=3\left(x\right)-3\left(1.1\right)$
$3\left(x-1.1\right)=3x-3.3$
Substitute $3\left(x-1.1\right)=3x-3.3$ in $3\left(x-1.1\right)=5x-5.3$
$3x-3.3=5x-5.3$
Subtract 5x on both sides,
$3x-3.3=5x-5.3$
$3x-5x-3.3=5x-5.3-5x$
$3x-5x-3.3=5x-5x-5.3$
The value of $3x-5x$ is $-2x$
The value of $5x-5x$ is 0
Substitute $3x-5x=-2x$ and $5x-5x=0$ in $3x-5x-3.3=5x-5x-5.3$
$-2x-3.3=-5.3$
$-2-3.3+3.3=-5.3+3.3$
The value of $-3.3+3.3$ is 0
The value of $-5.3+3.3$ is -2
Substitute $-3.3+3.3=0$ and $-5.3+3.3=-2$ in $-2x-3.3+3.3=-5.3+3.3$
$-2x=-2$
Divide by 2 on both sides,
$-\frac{2x}{2}=-\frac{2}{2}$
$-x=-1$
$x=1$

Do you have a similar question?